2014
DOI: 10.1371/journal.pone.0111326
|View full text |Cite
|
Sign up to set email alerts
|

Simplexide Induces CD1d-Dependent Cytokine and Chemokine Production from Human Monocytes

Abstract: Monocytes are major effector cells of innate immunity and recognize several endogenous and exogenous molecules due to the expression of wide spectrum of receptors. Among them, the MHC class I-like molecule CD1d interacts with glycolipids and presents them to iNKT cells, mediating their activation. Simplexide belongs to a novel class of glycolipids isolated from marine sponges and is structurally distinct from other immunologically active glycolipids. In this study we have examined the effects of simplexide on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…1 A–C). To exclude that the effect of characellide could be due to LPS contamination, a well-characterized stimulus for these cells (Loffredo et al 2014 ), PBMC were stimulated with characellide in the presence of polymyxin B (50 mg/ml), a potent inactivator of LPS (Kolomaznik et al 2018 ). Polymyxin B did not influence the capacity of characellide A to induce the release of CXCL8, IL-6, and TNF-α, whereas it almost completely suppressed the production of cytokines and chemokines induced by LPS (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 A–C). To exclude that the effect of characellide could be due to LPS contamination, a well-characterized stimulus for these cells (Loffredo et al 2014 ), PBMC were stimulated with characellide in the presence of polymyxin B (50 mg/ml), a potent inactivator of LPS (Kolomaznik et al 2018 ). Polymyxin B did not influence the capacity of characellide A to induce the release of CXCL8, IL-6, and TNF-α, whereas it almost completely suppressed the production of cytokines and chemokines induced by LPS (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Data are representative of five independent experiments obtained from different donors. *p < 0.05, **p < 0.01, ***p < 0.001 (Loffredo et al 2014). We hypothesized that characellide A could be involved in PBMC activation through the CD1d pathway.…”
Section: Cd1d Is Required For Pbmc Activation Induced By Characellide Amentioning
confidence: 98%
See 2 more Smart Citations
“…Despite the remarkable structural differences with the plakosides, the simplexides share a very similar biological profile, showing potent inhibitory activity of the proliferarion of T cells in the murine immune system when stimulated with concanavalin A through a noncytotoxic mechanism. Further biological studies demonstrated that the immunosuppressive effects of the simplexides are due to the induction that they exert on the expression and release of cytokines and chemokines from human monocytes by direct interaction with the CD1d receptors, expressed in these cells [ 138 ]. In addition, the simplexides induce the expansion of i NKT (natural killer T cells with an invariant T cell receptor alpha chain).…”
Section: Chemistry and Biology Of Atypical Glycolipidsmentioning
confidence: 99%